Simultaneous heat and water recovery from flue gas by membrane condensation: Experimental investigation. (25th February 2017) - Zhao, Shuaifei; Yan, Shuiping; Wang, David K.; Wei, Yibin; Qi, Hong; Wu, Tao; Feron, Paul H.M.
Graphical abstract: Highlights: Membrane condenser for water and heat recovery from flue gas is investigated. Effect of operational parameters on overall heat transfer coefficient is studied. Rise in gas flow rate or water temperature reduces overall recovery performance. Rise in water flow rate, gas temperature or humidity improves overall performance. This study offers a guideline in optimising parameters in membrane condensers. Abstract: A tubular ceramic membrane is investigated as the condenser for simultaneous heat and water recovery from flue gas. The effects of the operational parameters, such as fluid (gas and water) flow rates, temperatures of flue gas and coolant water, and flue gas humidity on the process performance in terms of mass and heat transfer across the membrane are studied. Particularly, the overall heat transfer coefficient is also evaluated. As the gas flow rate increases, water and heat transfer efficiencies and recoveries decline due to the reduced residence time. Increasing the water flow rate or lowing the coolant temperature can effectively improve mass and heat transfer efficiencies and recoveries. Increasing the temperature of the inlet gas can enhance water and heat fluxes and recoveries, but does not improve the overall heat transfer efficiency. The rise in flue gas humidity can dramatically improve water and heat transfer rates and the overall heat transfer coefficient, but has little effect on water and heat recoveries. These results offer a general guideline in optimising the operational parameters in low-grade heat recovery with membrane heat exchangers, and it may greatly advance the development of membrane condensation technology for practical low-grade heat recovery.